Quantitative study on in-cylinder combustion and heat release characteristic parameters of gasoline engine based on single variable sweeping tests. (5th May 2017) - Liu, Jingping; Zhu, Guohui; Fu, Jianqin; Xu, Zhengxin; Yao, Jun; Zhan, Zhangsong
Highlights: Sweeping tests about the influence factors of gasoline engine combustion rate were conducted. The influence factors of combustion characteristic parameters were quantitatively studied. The semi-empirical models for combustion characteristic parameters of gasoline engine were derived. The quantitative relations between combustion characteristic parameters and engine operating parameters were built. Abstract: The single variable sweeping tests about the influence factors of in-cylinder combustion and heat release processes of gasoline engine were carried out based on a special test engine with open electronic control unit (ECU). Through secondary development on tested data, the characteristic parameters of three stages of premixed combustion processes were quantitatively studied and the common rules were summarized. On this basis, the semi-empirical models for combustion characteristic parameters were derived, and the quantitative relations between combustion characteristic parameters and engine operating parameters, including speed, load, spark advance angle and excess air coefficient, etc., have been built. Furthermore, the proposed semi-empirical models were applied to other engines, which were proved to be of satisfactory accuracy and reliability. The effects of excess air coefficient, RGF, load and intake tumble on combustion rate are mainly reflected in SA (spark advance)-10% combustion duration rather than 10–90% combustion duration, and the spark advance angle has little influence on SA-50% combustion duration. The summarized common rules and the proposed semi-empirical models can be used to predict the combustion characteristic parameters of engine, which is helpful for simulating and optimizing the in-cylinder working process of engine especially in design and development stage.